Prevalence of high-grade squamous intraepithelial lesion within two years of large loop excision of the transformation zone at a tertiary hospital colposcopy clinic in Cape Town - Olujobi, Victor (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMed) -- Stellenbosch University, 2022.